KESEHATAN PADA ORANG LANJUT USIA (Kesehatan Mental dan Kesehatan Fisik) - Fauzia Nur Qonita; Nanda Annisa Salsabila; Niken Fitri Anjani; Syahnur Rahman (Fakultas Psikologi Universitas Wijaya Putra, 2021)
There will be a dramatic increase globally in those aged 80 or older, from about 137 million in 2017 to nearly 425 million in 2050. Aging has placed a rapidly increasing burden on health care and disease control. Improveing the quality of life of the elderly can be done through the role of the family, improving the quality of life of the elderly and improving the quality of life of the elderly. This study collected information and data about the health of the elderly, both physically and mentally, which then made up all the information or data that had been collected.